Review of the Japanese species of Paramerina (Diptera: Chironomidae: Tanypodinae), with a key to the known males - Niitsuma, Hiromi; Suzuki, Risa; Kato, Hideaki (Zootaxa, 2011)
The Japanese species of the genus Paramerina Fittkau, 1962 are reviewed based on studies of the type material and the specimens collected recently. Three species, P. kurobekogata Sasa et Okazawa, P. tokararesea Sasa et Suzuki and Krenopelopia amaminova Sasa, are treated as synonyms, and four species, P. yunouresia (Sasa), P. okigenga (Sasa), P. okimaculata Sasa and P. togavicea (Sasa et Okazawa), are recognized as valid. The adults, males and females, of the first two and the last species, and the pupa of the last species are redescribed. The pupae and larvae of the first two species, and the larva of the last species are described for the first time in this paper. Based on the examination of the holotype, the morphological features of P. okimaculata are discussed. The generic diagnosis for the larva is emended. A key to males of the known Japanese species is provided.